2021
DOI: 10.5811/westjem.2021.8.49485
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Means Counseling for Suicidal Adults in the Emergency Department: A Qualitative Study

Abstract: Introduction Lethal means counseling (to reduce access to firearms or other suicide methods) is a recommended critical yet challenging component of care of suicidal patients. Questions remain about communication strategies for those in acute crisis. Methods This qualitative study was an analysis of semi-structured interviews with English-speaking, community-dwelling adults with a history of lived-experience of suicidal ideation or attempts in themselves or a family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Nineteen eligible papers were identified (Figure 1), of which 16 addressed LMSC exclusively for firearms, 1 addressed LMSC exclusively for medications (40), and 2 addressed LMSC for both firearms and medications [ (41,42); Table 1]. Given the paucity of medication-related data, we briefly summarized findings on medication-related LMSC and focused our main analyses on firearm-specific LMSC.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen eligible papers were identified (Figure 1), of which 16 addressed LMSC exclusively for firearms, 1 addressed LMSC exclusively for medications (40), and 2 addressed LMSC for both firearms and medications [ (41,42); Table 1]. Given the paucity of medication-related data, we briefly summarized findings on medication-related LMSC and focused our main analyses on firearm-specific LMSC.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…In fact, securing firearms increased the chance of not having access to them when needed for personal or household protection. Firearm owners stated that their valuation of safety motivated them both to have easy access to firearms for protection and to practice responsible ownership (20,42,45,46,51,52,55). Responsible ownership included preventing unauthorized access to firearms and practicing safe handling (46,52,55), as well as introducing firearms to children and teaching them to respect firearms and handle them safely (20,46).…”
Section: Theme 4: Beliefs About Safety and Risks Of Secured And Unsec...mentioning
confidence: 99%
See 2 more Smart Citations
“…Initial testing of L2L with a tablet in an emergency department setting showed that it was highly acceptable across a broad range of provider roles (physicians, nurses, social workers). L2L addresses the lack of provider knowledge for different firearm and medication storage options ( 20 ). A survey showed that clinicians thought L2L would help them counsel suicidal adult patients on safe firearm storage options ( 21 ).…”
Section: Introductionmentioning
confidence: 99%